IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA DENGAN KONTEKS SOCIO-SCIENTIFIC ISSUE - Tia Apriliana Effendi; An Nuril Maulida Fauziah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aimed to describe the learning implementation of learning, improvement of critical thinking skills, and students’ response to the implementation of problem based learning model with socio-scientific issue on energy sources. This research used a pre-experimental design with one group pretest posttest design. The subject in this research were 30 students of VII C class in SMPN 42 Surabaya. Data were collected by observation, pretest and posttest, and questionnaires. The data was analyzed quantitatively. The research result showed that implementation of learning obtained high results with very good category in the first and second meeting. The critical thinking skills effectively improved with N-Gain score in medium category. The students gave a positive response and high interest in learning implementation. Based on the result, it can be concluded that implementation of problem based learning model with socio-scientific issue can improve students’ critical thinking skills.